Reevaluation of interpretive criteria for Haemophilus influenzae by using meropenem (10-microgram), imipenem (10-microgram), and ampicillin (2- and 10-microgram) disks. - Zerva, L (1996)
A collection of 300 Haemophilus influenzae clinical strains was used to assess in vitro susceptibility to carbapenems (meropenem, imipenem) by MIC and disk diffusion methods and to compare disk diffusion test results with two potencies of ampicillin disks (2 and 10 micrograms). The isolates included ampicillin-susceptible or- intermediate (167 strains), beta-lactamase-positive (117 strains), and beta-lactamase-negative ampicillin-resistant (BLNAR; 16 strains) organisms. Disk diffusion testing was performed with 10-micrograms meropenem disks from two manufacturers. Meropenem was highly active against H. influenzae strains (MIC50, 0.06 microgram/ml; MIC90, 0.25 microgram/ml; MIC50 and MIC90, MICs at which 50 and 90%, respectively, of strains are inhibited) and was 8- to 16-fold more potent than imipenem (MIC50, 1 microgram/ml; MIC90, 2 micrograms/ml). Five non-imipenem-susceptible strains were identified (MIC, 8 micrograms/ml), but the disk diffusion test indicated susceptibility (zone diameters, 18 to 21 mm). MIC values of meropenem, doxycycline, ceftazidime, and ceftriaxone for BLNAR strains were two- to fourfold greater than those for other strains. The performance of both meropenem disks was comparable and considered acceptable. A single susceptible interpretive zone diameter of > or = 17 mm (MIC, < = or 4 micrograms/ml) was proposed for meropenem. Testing with the 2-micrograms ampicillin disk was preferred because of an excellent correlation between MIC values and zone diameters (r = 0.94) and superior interpretive accuracy with the susceptible criteria at > or = 17 mm (MIC, < or = 1 microgram/ml) and the resistant criteria at < or = 13 mm (MIC, > or = 4 micrograms/ml). Among the BLNAR strains tested, 81.3% were miscategorized as susceptible or intermediate when the 10-micrograms ampicillin disk was used, while the 2-micrograms disk produced only minor interpretive errors (12.5%). Use of these criteria for testing H. influenzae against meropenem and ampicillin should maximize reference test and standardized disk diffusion test performance with the Haemophilus Test Medium. The imipenem disk diffusion test appears compromised and should be used with caution for detecting strains for which imipenem MICs are elevated.